Mood repair via attention refocusing or recall of positive autobiographical memories by adolescents with pediatric‐onset major depression. (3rd January 2015) - Kovacs, Maria; Yaroslavsky, Ilya; Rottenberg, Jonathan; George, Charles J.; Baji, Ildikó; Benák, István; Dochnal, Roberta; Halas, Kitti; Kiss, Enikő; Vetró, Ágnes; Kapornai, Krisztina
<x xml:space="preserve">Abstract</x> Background Impaired emotion regulation is increasingly recognized as a core feature of depressive disorders. Indeed, currently and previously depressed adults both report greater problems in attenuating sadness (mood repair) in daily life than healthy controls. In contrast, studies of various strategies to attenuate sad affect have mostly found that currently or previously depressed adults and controls were similarly successful at mood repair in the laboratory. But few studies have examined mood repair among depression‐prone youths or the effects of trait characteristics on mood repair outcomes in the laboratory. Methods Adolescents, whose first episode of major depressive disorder (MDD) had onset at age 9, on average (probands), and were either in remission or depressed, and control peers, watched a sad film clip. Then, they were instructed to engage in refocusing attention (distraction) or recalling happy memories. Using affect ratings provided by the youths, we tested two developmentally informed hypotheses about whether the subject groups would be similarly able to attenuate sadness via the two mood repair strategies. We also explored if self‐reported habitual (trait) mood repair influenced laboratory performance. Results Contrary to expectations, attention refocusing and recall of happy memories led to comparable mood benefits across subjects. Control adolescents reported significantly greater reductions in sadness than did depressed (Cohen's d = .48) or remitted (Cohen's d = .32) probands, regardless of mood repair strategy, while currently depressed probands remained the saddest after mood repair. Habitual mood repair styles moderated the effects of instructed (state) mood repair in the laboratory. Conclusions Whether depressed or in remission, adolescents with MDD histories are not as efficient at mood repair in the laboratory as controls. But proband‐control group differences in mood repair outcomes were modest in scope, suggesting that the abilities that subserve affect regulation have been preserved in probands to some degree. Further information about the nature of mood repair problems among youths with depression histories would help to better understand the clinical course of MDD and to design personalized interventions for depression.